Development of feed-based whole-cells inactivated bivalent vaccine and its immunoprotective ability against streptococcosis and motile aeromonad septicemia in red hybrid tilapia (Oreochromis spp.) - Monir, Md Shirajum (2021)
Streptococcosis and motile aeromonad septicemia (MAS) are well-known bacterial diseases in tilapia culture, which cause mass mortality with significant economic losses to aquaculture globally. As therapy resistance is an increasing problem, development of efficient fish vaccines seems to be an alternative to minimize the streptococcosis and MAS diseases. The development of feed-based monovalent vaccines in controlling these diseases has been attempted; however, the mechanism of immunity of feed-based bivalent vaccine against streptococcosis and MAS infections, and the cross-protective ability of these two diseases are still understudied. To explore the immunological role of the feed-based bivalent vaccine, we compared the immune responses of red hybrid tilapia after immunization with both feed-based bivalent and monovalent vaccines, and compared the relative percentage survival (RPS) and cross-immunization protections of red hybrid tilapia following challenged with Streptococcus iniae, Aeromonas hydrophila, S. agalactiae and A. veronii. A total of five groups of fish were vaccinated orally through two different techniques; bivalent vaccine (inactivated S. iniae and A. hydrophila) sprayed on feed pellets (BS group); bivalent vaccine (inactivated S. iniae and A. hydrophila) incorporated in fish feed (BI group); monovalent inactivated S. iniae and A. hydrophila vaccine separately incorporated into feed as monovalent S. iniae (MS group) and monovalent A. hydrophila (MA group); and control group (without vaccine). The feed based vaccines were delivered orally at 5% of body weight for five consecutive days and also the double booster doses were administered in the same manner on weeks 2 and 6. The haematological results revealed that BI vaccinated group exhibited significantly the highest (P < 0.05) number of leucocytes (45.39 ± 1.34 × 103 /µL) and granulocytes (7.68 ± 0.29 × 103 /µL) on weeks 3 post-vaccination. The lysozyme activity demonstrated a significant (P < 0.05) increase in BI vaccinated group particularly on 8 (313.77 units/mL) and 12 (303.62 units/mL) weeks post-vaccination. The significantly (P < 0.05) highest phagocytic activity was also observed in BI group (53.83%), while the lowest was obtained in BS group (37.33%) on weeks 12 post-vaccination. The enzyme-linked immunosorbent assay (ELISA) analysis showed that BI group developed a strong and significantly (P < 0.05) higher systemic and mucosal IgM responses against both S. iniae and A. hydrophila, and also cross-protective antigen S. agalactiae and A. veronii as compared to the BS vaccine and unvaccinated groups. On weeks 10 post-vaccination, all fish were challenged through the intraperitoneally (i.p.) route, where relative percentage survival (RPS) in the BI vaccinated group were observed 82.22 ± 3.85% when challenged with S. iniae, 77.78 ± 3.85% when challenged with A. hydrophila and 77.78 ± 3.85% when co-challenged with both S. iniae and A. hydrophila, which were significantly higher (P < 0.05) compared to the other groups. Simultaneously, the BI vaccinated group also showed significantly (P < 0.05) higher partial cross-protections following challenges with S. agalactiae (RPS at 60.00 ± 6.67%) and A. veronii (RPS at 57.78 ± 7.70%). Quantitative real-time PCR results also showed that the relative expressions of IL-1β, C-type lysozyme, TNF-α, TGF-β, CD4, MHC-I, MHC-II and IgT genes in the BI vaccinated fish spleen, head kidney and hindgut exhibited various significant (P < 0.05) rising trends following both the early-phase vaccination and post-infections. Notably, the highest relative expression of IL-1β, MHC-II and IgT genes in BI vaccinated group were observed in the co-infected (S. iniae and A. hydrophila) fish spleen (9.8 - fold), head kidney (9.6 - fold) and hindgut (24.5 - fold), respectively. Combining our results demonstrate that the BI vaccine could elicit significant immunological responses and this vaccine is highly effective to control S. iniae and A. hydrophila virulence in red hybrid tilapia, but have moderate efficacy when challenged with S. agalactiae and A. veronii. Nevertheless, this newly developed feed-based bivalent incorporated (BI) vaccine can effectively protect tilapia against streptococcosis and MAS infections, and also could offer a promising strategy for mass fish vaccination in aquaculture industry.